2022
DOI: 10.3389/fmars.2022.949428
|View full text |Cite
|
Sign up to set email alerts
|

PlanktoScope: Affordable Modular Quantitative Imaging Platform for Citizen Oceanography

Abstract: The oceans represent 97% of all water on Earth and contain microscopic, drifting life, plankton, which drives global biogeochemical cycles. A major hurdle in assessing marine plankton is the planetary scale of the oceans and the logistical and economic constraints associated with their sampling. This difficulty is reflected in the limited amount of scientifically equipped fleets and affordable equipment. Here we present a modular hardware/software open-source strategy for building a versatile, re-configurable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 33 publications
0
13
0
Order By: Relevance
“…Over the last few years, we have thus developed the PlanktoScope (see companion papers by Pollina et al, 2022 andMeŕiguet et al, 2022), an affordable, miniaturized, modular and evolvable, open source imaging platform for citizen oceanography. For a cost of less than 1000 US$ in parts, the PlanktoScope allows both quantitative imaging of microplankton communities through a fluidic module before their storage for total DNA/ RNA extraction and genetic analyses in the lab, and high-quality imaging/filming of individual cells or organisms under different types of illumination.…”
Section: Collecting Morphological and Behavioral Plankton Data At Seamentioning
confidence: 99%
See 4 more Smart Citations
“…Over the last few years, we have thus developed the PlanktoScope (see companion papers by Pollina et al, 2022 andMeŕiguet et al, 2022), an affordable, miniaturized, modular and evolvable, open source imaging platform for citizen oceanography. For a cost of less than 1000 US$ in parts, the PlanktoScope allows both quantitative imaging of microplankton communities through a fluidic module before their storage for total DNA/ RNA extraction and genetic analyses in the lab, and high-quality imaging/filming of individual cells or organisms under different types of illumination.…”
Section: Collecting Morphological and Behavioral Plankton Data At Seamentioning
confidence: 99%
“…Today we have developed all parts to assemble a stable P2 PlanktoKit 1.0 allowing any engaged seatizen to generate consistent plankton eco/morpho/genetic data directly in the field. The PlanktoKit 1.0, which costs less than $3,000 in parts, consists of a cruising-speed plankton collection system (von Ammon et al, 2020), a PlanktoScope (Pollina et al, 2022), a new cost-effective plankton DNA collection-kit we call the 'Lamprey', and a tablet computer to drive the PlanktoScope, record all contextual and meta-data, and visualize and record plankton images and movies. We have shown that these frugal tools deployed from sailing boats can generate consistent, planetary scale genetic (this paper) and morphological (Meŕiguet et al, 2022) data, paving the way for the Plankton Planet vision (Box 1).…”
Section: Toward Seatizen Field-aquascopes For Perennial Cooperative M...mentioning
confidence: 99%
See 3 more Smart Citations